2008
DOI: 10.17660/actahortic.2008.783.59
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Amelioration of Synthetic Turf Surfaces Through Irrigation

Abstract: Researchers have found that the surface temperatures of synthetic turf playing surfaces are significantly higher than natural turfgrass surfaces when exposed to sunlight. Reports indicate the surface temperatures of traditional synthetic turf can as much as 35-60 °C higher than natural turfgrass surface temperatures. Surface temperatures of infill synthetic turf systems have been reported to be as high as 93°C on a day when air temperatures were 37°C. Researchers have concluded that the heat transfer from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 2 publications
2
17
0
Order By: Relevance
“…Results from this study have shown that surface temperature of synthetic turf plots, installed as a complete system, vary substantially when exposed to the same environmental conditions, thus indicating that appropriate selection of synthetic turf products is essential, particularly in hot dry environments which are commonly experienced during Australian summers. Consistent with previous studies (Aoki, 2005;Williams and Pulley, 2003;Devitt et al, 2007;McNitt et al, 2008), our findings also indicated that surface temperature was influenced by weather variables including ambient temperature, solar radiation and humidity. As expected, increases in solar radiation and/or ambient temperature were associated with increased surface temperatures, and these two covariates were found to have the largest impact on surface temperature.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Results from this study have shown that surface temperature of synthetic turf plots, installed as a complete system, vary substantially when exposed to the same environmental conditions, thus indicating that appropriate selection of synthetic turf products is essential, particularly in hot dry environments which are commonly experienced during Australian summers. Consistent with previous studies (Aoki, 2005;Williams and Pulley, 2003;Devitt et al, 2007;McNitt et al, 2008), our findings also indicated that surface temperature was influenced by weather variables including ambient temperature, solar radiation and humidity. As expected, increases in solar radiation and/or ambient temperature were associated with increased surface temperatures, and these two covariates were found to have the largest impact on surface temperature.…”
Section: Discussionsupporting
confidence: 92%
“…Empirical evidence on the surface temperature difference between third generation (3G) synthetic turf and natural grass is limited, however, studies have demonstrated elevated surface temperatures on synthetic playing fields, particularly when exposed to direct sunlight (Aoki, 2005;Williams and Pulley 2003;Devitt et al 2007;McNitt et al, 2008). Recent research has focused on identifying and understanding how environmental variables impact on the surface temperature of 3G synthetic turf, and it is evident that surface temperature is directly related to ambient temperature (Devitt et al, 2007) and solar radiation (Aoki, 2005;Devitt et al, 2007;McNitt et al, 2008), and inversely related to humidity (Williams and Pulley, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The performance of the now commercialized artificial turf based on this fiber is promising. A main draw‐back remains: surface temperatures of synthetic turf are significantly higher than natural grass surfaces when exposed to sunlight,38 which can contribute to physiological stress of athletes and can cause heat‐related illnesses 39. This is still an unsolved problem that requires further research efforts.…”
Section: Discussionmentioning
confidence: 99%
“…These issues consist of the high initial costs, the rubber odour emanating from the pitch, the undue abrasiveness for athletes sliding on the pitch, resulting in abrasions and wounds that are subject to infection [3-6], the environmental fate of the several tonnes of plastic, rubber, and glue that make up a typical artificial-turf pitch and need to be discarded at the end of its playing life, the recurring doubts concerning the leachate quality from the pitch into the water table, the heavy metal contents of certain infill rubbers, and the possible harm from inhaling polycyclic aromatic hydrocarbons [7][8][9][10][11]. One particular drawback of rubber-infilled third-generation artificial turf lies in its very high summer pitch temperatures that can exceed 93 • C [12,13].…”
Section: Introductionmentioning
confidence: 99%